Isolation of insect parasitic fungi Corrdyceps spp. rich in bioactive beauvericin from Pu Mat National Park, Nghe An - Lan, Nguyễn Thị Thanh; Thúy, Đinh Thị Ngọc; Bình, Nguyễn Thị Thanh (Vietnam Journal of Biotechnology, 2016)
Insect parasitic fungi Cordyceps sp. B6 was isolated as single spores from fungi on the host insect pupae of Lepidoptera, collected at Pu Mat National Park, Nghe An, Vietnam. Cordyceps B6 strain was identified by the method of molecular biology, in which the DNA of the strain was extracted, cleaned and used as a template to amplify the gene segment using primers for ITS1 and ITS2. ITS gene segment of the strain was sequenced and compared to sequences in the GeneBank database using BLAST (NCBI). With the similarity of 99% compared to the corresponding gene fragment of Cordyceps takaomontana, Cordyceps B6 strain was identified as C. takaomontana. C. takaomontana B6 was best activated with liquid medium CT1 containing glucose 20 g/l, yeast extract 5 g / l, peptone 10 g/l, KH2PO4 1 g/l, 0.5 g MgSO4/l . In this medium, the density could reach 5 x 106 spores cells/ml after 7 days of culture. When surface fermentation performed in appropriate conditions (25 °C, pH= 7, light intensity 200 lux, humidity 80%), the fresh weight of 18.72 g/vial of spore cells and 2.09 mg of active beauvericin per gram of freeze-dry weight were obtained after 45 days of culture. With a high concentration of active beauvericin, C. takaomontana B6 could be considered as a potential source for development of functional food and raw materials for the pharmaceutical industry